Петербургские повести - Гоголь Николай Васильевич (Школьная библиотека, 2002)
Экземпляры: ф.23 (2003) / Инвентарный номер: 47175 / Цена: / Сис.шифр: 84(2Рос=Рус)1-44 / Авт.знак: Г 58 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1-44